Vitamin C intake from diary recordings and risk of breast cancer in the UK Dietary Cohort Consortium. - Hutchinson, J; Lentjes, M; Greenwood, D; Burley, V; Cade, J; Cleghorn, C; Threapleton, D; Key, T; Cairns, B; Keogh, R; Dahm, C; Brunner, E; et al. (2012)
BACKGROUND/OBJECTIVES: Vitamin C intake has been inversely associated with breast cancer risk in case-control studies, but not in meta-analyses of cohort studies using Food Frequency Questionnaires, which can over-report fruit and vegetable intake, the main source of vitamin C. This is the first study to investigate associations between vitamin C intake and breast cancer risk using food diaries. SUBJECTS/METHODS: Estimated dietary vitamin C intake was derived from 4-7 day food diaries pooled from five prospective studies in the UK Dietary Cohort Consortium. This nested case-control study of 707 incident breast cancer cases and 2144 matched controls examined breast cancer risk in relation to dietary vitamin C intake using conditional logistic regression adjusting for relevant covariates. Additionally, total vitamin C intake from supplements and diet was analysed in three cohorts. RESULTS: No evidence of associations was observed between breast cancer risk and vitamin C intake analysed for dietary vitamin C intake (odds ratios (OR)=0.98 per 60 mg/day, 95% confidence interval (CI): 0.88-1.09, P (trend)=0.7), dietary vitamin C density (OR=0.97 per 60 mg/day, 95% CI: 0.87-1.07, P (trend)=0.5 ) or total vitamin C intake (OR=1.01 per 60 mg/day, 95% CI: 0.99-1.03, P (trend)=0.3). Additionally, there was no significant association for post-menopausal women (OR=1.02 per 60 mg/day, 95% CI: 0.99-1.05, P (trend)=0.3). CONCLUSIONS: This pooled analysis of individual UK women found no evidence of significant associations between breast cancer incidence and dietary or total vitamin C intake derived uniquely from detailed diary recordings.